2006
DOI: 10.3177/jnsv.52.428
|View full text |Cite
|
Sign up to set email alerts
|

Soyfood Intake in the Prevention of Breast Cancer Risk in Women: A Meta-Analysis of Observational Epidemiological Studies

Abstract: Summary Many studies have suggested that the intake of soy products may protect against the occurrence of breast cancer because of the considerable amount of isoflavones they contain. To review the results of the observational studies, we performed this metaanalysis of the relevant literature. We searched Medline for reports that examined the association between soyfood consumption (or isoflavone intake) and breast cancer risk from January 1966 to April 2006. The random-effects model was used to estimate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 49 publications
7
56
0
5
Order By: Relevance
“…A meta-analysis of 47 studies indicated that soy or soy isoflavone can significantly reduce the level of folliclestimulating hormone and luteinizing hormone in premenopausal women (Hooper et al, 2009). Several previous studies support the inverse association between soy food and breast cancer risk among Asian people, but a non-significant association is found among Western people (Qin et al, 2006;Wu et al, 2008;Dong et al, 2011). The major reason may come from the less soy food consumed by Western people than Chinese people.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 47 studies indicated that soy or soy isoflavone can significantly reduce the level of folliclestimulating hormone and luteinizing hormone in premenopausal women (Hooper et al, 2009). Several previous studies support the inverse association between soy food and breast cancer risk among Asian people, but a non-significant association is found among Western people (Qin et al, 2006;Wu et al, 2008;Dong et al, 2011). The major reason may come from the less soy food consumed by Western people than Chinese people.…”
Section: Discussionmentioning
confidence: 99%
“…Soy intakes yield a reduced risk for prostate cancer and breast cancer in recent meta-analyses among Asian population although dose-response relationship is not clear (Qin et al, 2006;Yan and Spitznagel, 2009;Dong and Qin, 2011). However the protective effect of soy isoflavones is not significantly found among non-Asian populations who soybeans and soy-related products intake is not frequent (Yan and Spitznagel, 2009;Dong and Qin, 2011).…”
Section: Reduction In Cancer Riskmentioning
confidence: 96%
“…59 However, this is not always consistent, especially in populations with low phytoestrogen intakes. 8,13,60,61 The possible mechanism of action through which phytoestrogens may act is often related with their weak estrogenic activity, 4 but it has even been suggested that phytoestrogens might simply reflect a healthy lifestyle. 8 In our study, healthy lifestyle and anthropometric characteristics, which have been associated with risk of hormone-related diseases, were statistically associated with lignans, enterolignans and equol, but no differences were shown for total phytoestrogens, isoflavones or coumestans.…”
Section: P-valuementioning
confidence: 99%
“…4,8,10 Furthermore, phytoestrogens may reduce oxidative stress by activating intracellular kinase cascades, leading to acute activation of endothelial nitric oxide synthase and modulating redox-sensitive gene transcription via NF-kB (nuclear factor-kB) and Nrf2 (nuclear factor erythroid 2-related factor 2). 11,12 A meta-analysis investigating the relationship between soy foods, isoflavone intakes and breast cancer showed an inverse association in Asian populations, but not in Western populations (Europe and US), 13 which tend to have low phytoestrogen intake.…”
Section: Introductionmentioning
confidence: 99%